2008
DOI: 10.1111/j.1528-1167.2008.01491.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid astrocyte and microglial activation following pilocarpine‐induced seizures in rats

Abstract: SUMMARYAstrocyte and microglial activation occurs following seizures and plays a role in epileptogenesis. However, the precise temporal and spatial response to seizures has not been fully examined. The pilocarpine model of temporal lobe epilepsy was selected to examine glial changes following seizures because morphological changes in the hippocampus closely mimic the human condition. Astrocytic and microglial changes in the hippocampus were examined during the first 5 days after pilocarpine-induced seizures in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
142
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(159 citation statements)
references
References 38 publications
(49 reference statements)
12
142
1
1
Order By: Relevance
“…In the KA-induced seizure group, MAP and HR were increased by 21 Ϯ 4 mmHg ( p ϭ 0.008) and 32 Ϯ 7 bpm ( p ϭ 0.0001), respectively, compared with the vehicle-treated group (Fig. 3 B, C): the findings support the notion that seizure is the cause of the dramatic increase in sympathetic nerve activity, tachycardia, and pressor effects (Sakamoto et al, 2008;Bealer et al, 2010). Bilateral microinjection of PBS (50 nl) had a transient and nonsignificant effect on MAP, HR, and SNA, that lasted for only a few minutes (Fig.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…In the KA-induced seizure group, MAP and HR were increased by 21 Ϯ 4 mmHg ( p ϭ 0.008) and 32 Ϯ 7 bpm ( p ϭ 0.0001), respectively, compared with the vehicle-treated group (Fig. 3 B, C): the findings support the notion that seizure is the cause of the dramatic increase in sympathetic nerve activity, tachycardia, and pressor effects (Sakamoto et al, 2008;Bealer et al, 2010). Bilateral microinjection of PBS (50 nl) had a transient and nonsignificant effect on MAP, HR, and SNA, that lasted for only a few minutes (Fig.…”
Section: Resultssupporting
confidence: 76%
“…Seizure-induced cardiovascular autonomic dysfunction is a common cause of sudden unexpected death in epilepsy (SUDEP), which accounts for 5%-17% deaths in people with epilepsy (Sakamoto et al, 2008;Surges et al, 2009;Bardai et al, 2012;Massey et al, 2014). The rostral ventrolateral medulla (RVLM) contains sympathetic premotor neurons (C1), which are a subset of catecholaminergic neurons that express all of the enzymes necessary for the synthesis of adrenaline (Schreihofer and Guyenet, 1997;Phillips et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…approximately on days 1-3, immediate activation of astrocytes and microglia [8] and similar astrogliosis were demonstrated after KA administration to the rat hippocampus [21,22]. Two to three weeks after KA application, the astrocytes displayed changed morphology, but there were no changes after 90 days.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, both pre-clinical and clinical studies have demonstrated the presence of glial abnormalities in epileptic regions (Griffin et al, 1995;Lee et al, 2007;Somera-Molina et al, 2007;Shapiro et al, 2008). Epileptic brain is characterized by profound astrogliotic reaction with morphological and functional changes in astrocytes (Seifert et al, 2006).…”
Section: Introductionmentioning
confidence: 99%